2015
DOI: 10.1186/s13104-015-1583-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hemoglobin S trait among blood donors: a cross-sectional study

Abstract: BackgroundSickle cell trait (SCT) or Hemoglobin S (HbS) trait which is due to inheritance of an abnormal hemoglobin (Hb) gene from one parent and a normal gene from the other has been known to be common among people of African descent. Individuals with SCT may find themselves in the blood donor population without knowing their ‘carrier’ status and this may have severe consequences on their health as well as that of a recipient, particularly if they happen to be a sickle cell disease patient. The aim of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 15 publications
4
26
1
4
Order By: Relevance
“…This mutation consequently changes the physico-chemical properties of the haemoglobin molecule [12]. A person who inherits haemoglobin S from one parent and haemoglobin A (normal gene) from the other has a sickle cell trait (SCT) or is said to be a carrier of sickle cell disease [13]. The prevalence of sickle cell trait (SCT) is highest in Africans and people of African descent.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation consequently changes the physico-chemical properties of the haemoglobin molecule [12]. A person who inherits haemoglobin S from one parent and haemoglobin A (normal gene) from the other has a sickle cell trait (SCT) or is said to be a carrier of sickle cell disease [13]. The prevalence of sickle cell trait (SCT) is highest in Africans and people of African descent.…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria probably has the highest number of people with the trait, not just because of its high population but also because of a high prevalence of 25-30% [9] . The distributions in other parts of Africa are between 10-15% for Liberia, Ghana and Uganda [10][11][12] , respectively, Cameroon and the Republic of Gabon, a central African country, have a prevalence of 19 and 22%, respectively, closer to the prevalence in Nigeria than to other African countries [13,14] . Review of data from two decades of newborn screening in the United States revealed a prevalence of 1.5% [15] , but the prevalence in African Americans is about 8% [16] , which is similar to that of other African populations who migrated out of Africa as a result of the slave trade.…”
Section: Epidemiologymentioning
confidence: 97%
“…Em Gana, país da África ocidental, uma pesquisa realizada em um banco de sangue, mostrou que, entre 150 doadores, 17 (11,3%) eram portadores do traço falcêmico. Desses, somente 4 (2,7%) tinham conhecimento da sua condição 18 . Já, na Alemanha, um estudo realizado com dados de 37.838 recém-nascidos, evidenciou que apenas 0,2% deles eram portadores do traço falcêmico 19 .…”
Section: Cançado E Jesusunclassified
“…Situação semelhante ocorre em Gana, onde se encontrou uma proporção de 12 homens para cada mulher doadora de sangue. Esse predomínio do sexo masculino na doação de sangue pode ser justificado por algumas condições fisiológicas femininas, tais como gravidez, lactação e menstruação, que têm restrição na doação de sangue 18 . O presente estudo traz algumas limitações, entre elas destaca-se a ausência de etnia nos dados dos doadores.…”
Section: Cançado E Jesusunclassified